Fetal lung hypoplasia: biochemical and structural variations and their possible significance. Issue 8 (August 1981) - Wigglesworth, J S; Desai, R; Guerrini, P
Abstract : Quantitative biochemical criteria for lung growth and maturation were compared with the histological appearances in hypoplastic lungs from 20 fetuses and newborn infants. Cases associated with oligohydramnios showed a characteristic series of changes with narrow airways, retardation of epithelial and interstitial growth, delay in development of blood-air barriers, and low concentrations of phospholipid phosphorus, lecithin phosphorus, total palmitate, and lecithin palmitate. The growth and maturation arrest appeared to affect the peripheral part of the acinus. Examples of other types of lung hypoplasia showed different features. Hypoplastic lungs from infants with normal or increased amniotic fluid were of mature structure with phospholipid concentrations similar to those of infants with normally developed lungs at term. The hypoplastic left lung in 2 cases of congenital diaphragmatic hernia had an immature structure with low phospholipid concentrations, whereas the right lung has structurally and biochemically more mature. It is suggested that fetal lung growth may be impaired by any influence which reduces thoracic volume but that maturation arrest is due specifically to loss of the ability to retain lung liquid.